GILZ as a Mediator of the Anti-Inflammatory Effects of Glucocorticoids - Ronchetti, Simona; Migliorati, Graziella; Riccardi, Carlo (Frontiers in Endocrinology, 2015)
Glucocorticoid-Induced Leucine Zipper (GILZ) is a dexamethasone-inducible gene that mediates glucocorticoid (GC) actions in a variety of cell types, including many cells of immune system. In particular, GILZ can control T cell activities such as activation and differentiation, mainly through its ability to homo- and hetero-dimerize with partner proteins like NF-κB, Ras and C/EBP. These protein-protein interactions control the regulation of proinflammatory target genes. A number of in vitro and in vivo studies using mouse models of inflammatory diseases demonstrate an anti-inflammatory role for GILZ. Here we summarize those studies that make GILZ eligible as an anti-inflammatory protein through which glucocorticoids can act. These findings permit the future development of pharmacological tools that mimic the therapeutic effects of GCs while avoiding the detrimental ones.